Intracellular regulators of neuronal sprouting: II. Phosphorylation reactions in isolated growth cones - Hyman, C (J Neurosci, 1987)
Mechanisms potentially involved in the regulation of neurite growth were investigated. Since both the phosphatidylinositol (PI) pathway and protein kinase C have been implicated in transmembrane signal transduction, protein and lipid phosphorylation reactions were examined in intact growth cone particles (GCPs) isolated from fetal rat brain. Three major substrates of Ca2+-dependent phosphorylation were observed: proteins of 40 and 46 kDa and an acidic 80 kDa species separated in 2D PAGE (pp40, pp46, and pp80ac). The pp40 and pp80ac substrates had similar rates of 32P incorporation, whereas that of pp46 was more rapid. The importance of protein kinase C in growth cone function is indicated by the enhancement of phosphorylation of the 3 major substrates by the phorbol ester 12-O-tetradecanoylphorbol 13-acetate (TPA). An examination of the Ca2+-dependent 32P incorporation into pp40 and pp46 revealed serine to be the only amino acid phosphorylated under these conditions. A rapidly metabolized pool of phosphoinositides was observed in GCPs. This suggests the presence of the Pl pathway's enzymes in this fraction. Inositol trisphosphate (IP3) was found to stimulate the phosphorylation of pp40 and pp80ac, indicating a possible link between the activation of the PI pathway and protein phosphorylation. Our findings demonstrate the prominence of the PI pathway and of Ca2+-dependent protein phosphorylation in the growth cone and may suggest the involvement of these mechanisms in growth- factor signal transduction.